Herbal incense-related sudden death: case report. (4th March 2017) - Dilber, Dario; Barić, Hrvoje; Novinščak, Tomislav; Čerkez-Habek, Jasna
Abstract: Currently, there are over 100 legally available synthetic cannabimimetics (SCBs). Serious adverse effects and deaths have been related to use of these substances. Despite their known hazards, many of them are still not banned for use in Croatia and grow in popularity among drug users. We report the case of a young man who suffered a cardiorespiratory arrest and eventually died several hours after smoking herbal incense containing a sprayed mixture of SCBs and consuming alcohol. He had no history of health problems and the autopsy revealed no pathological findings. We discuss hazards related to herbal incense smoking and draw attention to the rise in a number of cases related to use of SCBs in our community.